Plasma diagnostic of gliding arc discharge at atmospheric pressure - Hameed, T. A.; Kadhem, S. J. (Iraqi Journal of Science, 2019)
A gliding arc discharge (GAD) with a water spray system was constructed. A non-thermal plasma, generated between two V shaped electrodes in an ambient argon driven by 100 Hz AC voltage, was investigated using optical emission spectroscopy (OES) with different gas flow rates (0.5, 1, 1.5, 2 , 2.5 , 3 1/min). Boltzmann plot method was used to calculate electron temperature (Te) and electron density (ne). The electrodes design was spectrally recognized and its Te value was about 0.588-0.863 eV, while the ne value of 6.875Ã—1017-10.938Ã—1017 cm-3. The results of the plasma diagnostics generated by gliding arc showed that increasing gas flow rates was associated with decreased electron temperature (Te), Debye length, and Debye Number, along with decreased electron density (ne) and plasma frequency.